Auditory gating in adults with dyslexia: An ERP account of diminished rapid neural adaptation. Issue 11 (November 2019) - Peter, Beate; McCollum, Hunter; Daliri, Ayoub; Panagiotides, Heracles
Highlights: Dyslexia is associated with reduced neural adaptation. P2 auditory gating was preserved in dyslexia. Reduced N1 gating in individuals with dyslexia was linked to their poor word representation. Abstract: Objective: A recent functional magnetic resonance imaging (fMRI) study of adults with dyslexia showed a general deficit in suppressing responses to various types of repetitive stimuli. This diminished neural adaptation may interfere with implicit learning and forming stable word representations. With fMRI, spatial but not temporal characteristics of the adaptation response could be identified. We address this knowledge gap using event-related potentials. Methods: Fourteen adults with dyslexia and 14 controls participated in an auditory gating paradigm using tone pairs. Response amplitudes and latencies for N1 and P2 were measured. Participants also compared word pairs consisting of identical or subtly different words, a task requiring stable word representations. Results: Only the controls showed a robust gating effect in an attenuated N1 response to the second tone relative to the first. The dyslexia group was less accurate than the controls in detecting word differences. The N1 gating magnitude was associated with this detection accuracy. Conclusions: Neural adaptation occurs by approximately 100 ms after stimulus presentation and is diminished in adults with dyslexia. This complements fMRI findings of relevant brain regions by implying a time window representing sensory and pre-attentive auditory processes. Significance: The association between gating magnitude and word discrimination contributes to a neurophysiological account of underspecified word representations.